Kesadaran Hukum Masyarakat Muslim terhadap Mediasi di Era Digital - Nasruddin; Agus Muchsin; M. Ihsan Darwis; Rahmawati; Islamul Haq (Cv. Kalimasada Group, 2025)
The rapid advancement of digital technology has fundamentally transformed various dimensions of human life, including the mechanisms of legal dispute resolution. This study aims to comprehensively analyze the legal awareness of the Muslim community in Parepare City, South Sulawesi, regarding the implementation of electronic mediation (e-mediation) in the digital era. Operating within the framework of the Supreme Court Regulation (PERMA) Number 3 of 2022, the shift from conventional face-to-face mediation to virtual platforms presents significant sociological, psychological, and theological challenges. This research employs a qualitative descriptive method with normative-theological and empirical-juridical approaches, utilizing data from the Parepare Religious Court, Parepare Police Department, and the National Land Agency of West Bacukiki. The findings indicate that while the Muslim community in Parepare demonstrates a high preference for non-litigation dispute resolution, heavily influenced by the local culture of Siri' na Pacce and the Islamic concept of Islah (peacemaking), their adoption of fully digital mediation remains sub-optimal. The primary inhibiting factors include a stark digital literacy deficit, unstable internet infrastructure, privacy concerns, and most crucially, the loss of emotional intuition (